Chiral cyclopentadienylruthenium sulfoxide catalysts for asymmetric redox bicycloisomerization - Trost, Barry M.; Ryan, Michael C.; Rao, Meera (Beilstein Journal of Organic Chemistry, 2016)
A full account of our efforts toward an asymmetric redox bicycloisomerization reaction is presented in this article. Cyclopentadienylruthenium (CpRu) complexes containing tethered chiral sulfoxides were synthesized via an oxidative [3 + 2] cycloaddition reaction between an alkyne and an allylruthenium complex. Sulfoxide complex 1 containing a p-anisole moiety on its sulfoxide proved to be the most efficient and selective catalyst for the asymmetric redox bicycloisomerization of 1,6- and 1,7-enynes. This complex was used to synthesize a broad array of [3.1.0] and [4.1.0] bicycles. Sulfonamide- and phosphoramidate-containing products could be deprotected under reducing conditions. Catalysis performed with enantiomerically enriched propargyl alcohols revealed a matched/mismatched effect that was strongly dependent on the nature of the solvent.
Keywords: asymmetric catalysis; [3.1.0] bicycles; [4.1.0] bicycles; cycloisomerization; 1,6-enyne; 1,7-enyne; ruthenium catalysis; sulfoxide